Ancient night - Álvarez Hernández, David Daniel; Bowles, David (David O.) (Levine Querido, 2023)
"Ancient Night is a twist on two Nahua traditions: the rabbit which the Feathered Serpent placed on the moon, and the Lord Opossum who ruled the earth when humans were first created, who stole fire from the gods to keep them warm."--